Negative electrode, lithium-ion secondary battery, and lithium-ion secondary battery module

JP2026165512APending Publication Date: 2026-10-14AESC JAPAN LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025057929
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、負極活物質層中の凝集物の発生を抑制できながら、負極活物質層と負極集電体層との密着性を向上できる負極を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165512000001_ABST
    Figure 2026165512000001_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode that can suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer. [Solution] A negative electrode comprising a negative electrode active material layer and a negative electrode current collector layer, wherein the negative electrode active material layer comprises a silicon-based active material and a polycarboxylic acid polymer (P1) having a weight-average molecular weight Mw of 550,000 or more and 950,000 or less.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a negative electrode, a lithium ion secondary battery, and a lithium ion secondary battery module.

BACKGROUND ART

[0002] Carbon-based active materials and silicon-based active materials are known as negative electrode active materials for lithium ion secondary batteries. Silicon-based active materials have attracted attention in that lithium ion secondary batteries with higher capacity can be obtained compared to the case of using carbon-based active materials.

[0003] Patent Document 1 describes a method for producing a negative electrode having a negative electrode current collector and a negative electrode active material layer, the method including a step of forming the negative electrode active material layer by compressing a negative electrode mixture layer formed on the negative electrode current collector, wherein the negative electrode mixture layer contains a negative electrode material, the negative electrode material contains a negative electrode active material with a graphite particle content of 70 mass% or more, and the specific surface area of the graphite particles is 1.0 m 2 / g or more and 2.5 m 2 / g or less, and the molding pressure required to compact the graphite particles uniaxially to a density of 1.7 g / cm 3 is 20 MPa or less. The document describes that the method for producing a negative electrode can provide a method for producing a negative electrode and a negative electrode that can suppress swelling of the negative electrode provided with the negative electrode active material layer.

[0004] Patent Document 2 describes a negative electrode for lithium ion batteries, which comprises an active material including a silicon-based active material; nanoscale conductive carbon; and a polymer binder including poly(acrylamide-co-acrylate) having at least about 5 mol% of acrylate moieties and at least about 5 mol% of acrylamide moieties.

PRIOR ART DOCUMENTS

PATENT DOCUMENTS

[0005]

PATENT DOCUMENT 1

[0006] In lithium-ion secondary batteries using silicon-based active materials as the negative electrode active material, the expansion and contraction of the silicon-based active material during charging and discharging sometimes caused the negative electrode active material layer to detach from the negative electrode current collector layer.

[0007] The present invention provides a negative electrode that can suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer. [Means for solving the problem]

[0008] The inventors diligently conducted research to achieve the above objectives. As a result, they discovered for the first time that by including a polycarboxylic acid polymer having a predetermined molecular weight in the negative electrode active material layer containing a silicon-based active material, it is possible to suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer, thus completing the present invention.

[0009] According to the present invention, the following negative electrode, lithium-ion secondary battery, and lithium-ion secondary battery module are provided.

[0010] [1] It comprises a negative electrode active material layer and a negative electrode current collector layer, The negative electrode comprises a silicon-based active material layer and a polycarboxylic acid polymer (P1) having a weight-average molecular weight Mw of 550,000 or more and 950,000 or less. [2] The negative electrode according to [1] above, wherein the polycarboxylic acid polymer (P1) contains an alkali metal salt of a polycarboxylic acid. [3] The negative electrode according to [2] above, wherein the alkali metal salt of the polycarboxylic acid includes a lithium salt of the polycarboxylic acid. [4] The negative electrode according to the above [2], wherein the alkali metal salt of the polycarboxylic acid comprises lithium polyacrylate. [5] The silicon-based active material is selected from the group consisting of SiO x (0<x≦2), Si / C containing Si-C composite particles, and Si, and the negative electrode according to any one of the above [1] to [4], comprising one or more selected from the group. [6] The negative electrode according to any one of the above [1] to [5], wherein when the total mass of the negative electrode active material layer is taken as 100% by mass, the content of the polycarboxylic acid-based polymer (P1) in the negative electrode active material layer is 0.1% by mass or more and 10% by mass or less. [7] The negative electrode according to any one of the above [1] to [6], wherein when the total mass of the negative electrode active material layer is taken as 100% by mass, the content of the silicon-based active material in the negative electrode active material layer is 1% by mass or more and 80% by mass or less. [8] The negative electrode according to any one of the above [1] to [7], wherein the negative electrode active material layer further comprises a synthetic rubber as a binder. [9] The negative electrode according to the above [8], wherein the synthetic rubber comprises a styrene-butadiene-based rubber.

[10] The negative electrode according to any one of the above [1] to [9], having a peel strength measured by the following method 1 of 10 N / mm or more. (Method 1) The negative electrode is cut into a size of 10 mm × 100 mm to prepare a test piece. Next, using a tensile tester, under the conditions of a tensile speed of 10 mm / min and a temperature of 25°C, the test piece is pulled until the tensile strength per cross-sectional area of the test piece reaches 15 N / mm 2 . Subsequently, using a peel tester, under the conditions of a lifting speed of 50 mm / min and a temperature of 25°C, the negative electrode active material layer of the test piece is lifted in a 90° direction to measure the peel strength.

[11] The negative electrode according to any one of the above [1] to

[10] , having a cell expansion rate measured by the following method 2 of 4.1% or less. (Method 2) For the cell produced by the <Cell Production Method> described below, the cell expansion rate is measured by the <Cell Expansion Rate Measurement Method> described below. <Cell Production Method> Lithium nickel cobalt manganese oxide (LiNi 0.9 Co 0.05 Mn 0.05 O₂) 97.5 parts by mass, 1.5 parts by mass of polyvinylidene fluoride, and 1.0 part by mass of multi-walled carbon nanotubes, to the solid content consisting of the above, N-methyl-2-pyrrolidone is added to prepare a positive electrode active material slurry. Next, after applying the positive electrode active material slurry to both surfaces of an aluminum foil, drying is performed to obtain a positive electrode laminate composed of the positive electrode active material layer and the aluminum foil. Next, the positive electrode laminate is pressed so that the density of the positive electrode active material layer is 3.50 g / cm 3 , to obtain a positive electrode. Next, an electrode laminate in which the negative electrode, a separator, the positive electrode, a separator, and the negative electrode are arranged in this order, and a non-aqueous electrolyte are placed inside a laminate outer package. Next, a negative electrode tab is connected to the negative electrode, and a positive electrode tab is connected to the positive electrode, respectively, and the periphery of the laminate outer package is sealed to produce a cell. <Cell Expansion Rate Measurement Method> The cell is placed in a constant temperature bath at 25°C. Next, the cell is charged at a constant current at a charge rate of 0.05C until the upper limit voltage reaches 4.25V, and after the voltage reaches 4.25V, the cell is charged at a constant voltage until the total charging time reaches 22 hours. Next, the cell is discharged at a constant current at a discharge rate of 1 / 3C until the lower limit voltage reaches 2.5V. After discharging, the cell is allowed to stand for 48 hours in a constant temperature bath at 45°C. Next, the cell expansion rate is calculated from the following formula (1). Formula (1): (The cell expansion rate) = {(Thickness of the cell after being left to stand for 48 hours in the constant temperature bath at 45°C after charge and discharge) − (Thickness of the cell before charging)} / (Thickness of the cell before charging) × 100

[12] The negative electrode according to any one of the above [1] to

[11] , wherein the direct current resistance measured by the following Method 3 is 5.0 mΩ or less. (Method 3) For cells prepared according to the <Method for Manufacturing Cells> described below, the DC resistance is measured according to the <Method for Measuring DC Resistance> described below. <How to create cells> Lithium nickel-cobalt manganese oxide (LiNi 0.9 Co 0.05 Mn 0.05 A cathode active material slurry is prepared by adding N-methyl-2-pyrrolidone to a solid content consisting of 97.5 parts by mass of O2, 1.5 parts by mass of polyvinylidene fluoride, and 1.0 part by mass of multi-walled carbon nanotubes. Next, the cathode active material slurry is applied to both sides of an aluminum foil and dried to obtain a cathode laminate consisting of a cathode active material layer and the aluminum foil. Then, the cathode laminate is subjected to a procedure where the density of the cathode active material layer is 3.50 g / cm³. 3 Press it in this manner to obtain the positive electrode. Next, an electrode laminate in which the negative electrode, separator, positive electrode, separator, and negative electrode are arranged in this order, and a non-aqueous electrolyte is placed inside a laminate casing. Then, a negative electrode tab is connected to the negative electrode and a positive electrode tab is connected to the positive electrode, and the laminate casing is sealed to create a cell. <Method for measuring DC resistance> The cell is placed in a constant temperature bath at 25°C. Next, the cell is charged to a state of charge (SOC) of 50%. Then, using a charge / discharge device, current is passed through the cell at 0.5C for 30 seconds, 1.0C for 30 seconds, and 2.0C for 30 seconds, and the voltage at 0.5C, 1.0C, and 2.0C is measured, respectively. Next, points corresponding to each voltage are plotted on a graph with the current value on the horizontal axis and the voltage on the vertical axis, and the slope of the three points is calculated to obtain the DC resistance.

[13] The negative electrode according to any one of the above [1] to

[12] , wherein the negative electrode active material layer further contains graphite.

[14] The negative electrode according to

[13] above, wherein, when the entire negative electrode active material layer is considered to be 100% by mass, the content of graphite in the negative electrode active material layer is 20% by mass or more and 99% by mass or less.

[15] The negative electrode according to any one of the above [1] to

[14] , wherein the negative electrode active material layer further comprises a conductive additive.

[16] The negative electrode according to

[15] above, wherein the conductive additive includes a carbon material.

[17] The negative electrode according to

[16] , wherein the carbon material includes carbon nanotubes.

[18] The negative electrode described above, wherein the negative electrode current collector layer includes copper foil, according to any one of [1] to

[17] above.

[19] The negative electrode described in any of the above [1] to

[18] , Positive electrode and, A lithium-ion secondary battery equipped with a separator.

[20] A lithium-ion secondary battery module comprising the lithium-ion secondary battery described above

[19] . [Effects of the Invention]

[0011] According to the present invention, it is possible to provide a negative electrode that can suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer. [Brief explanation of the drawing]

[0012] [Figure 1] This is a schematic cross-sectional view illustrating an example of a lithium-ion secondary battery according to this embodiment. [Modes for carrying out the invention]

[0013] Embodiments of the present invention will be described below with reference to the drawings. In all drawings, similar components are denoted by the same reference numeral, and explanations are omitted where appropriate. Furthermore, the drawings are schematic and do not necessarily correspond to actual dimensional proportions. In the specification, unless otherwise specified, the notation "A to B" regarding a numerical range means A or greater and B or less. For example, 1 to 5% means 1% or greater and 5% or less.

[0014] 1. Negative electrode The negative electrode of this embodiment comprises a negative electrode active material layer and a negative electrode current collector layer, wherein the negative electrode active material layer contains a silicon-based active material and a polycarboxylic acid polymer (P1) having a weight-average molecular weight Mw of 550,000 or more and 950,000 or less. The negative electrode of this embodiment, having the above-described configuration, can suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer. Furthermore, the negative electrode of this embodiment, having the above-described configuration, can also achieve the effect of suppressing expansion and contraction during charging and discharging of the resulting lithium-ion secondary battery, and the effect of reducing the DC resistance of the resulting lithium-ion secondary battery.

[0015] Although the mechanism by which the negative electrode of this embodiment solves the above-mentioned problems is not clear, it is thought that by having the weight-average molecular weight Mw of the polycarboxylic acid polymer (P1) within the above numerical range, aggregation of the polycarboxylic acid polymer (P1) can be reduced, maintaining the uniformity of the negative electrode active material layer, while improving the adhesion between the polycarboxylic acid polymer (P1) and other materials in the negative electrode active material layer. This is thought to suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer. Furthermore, the negative electrode of this embodiment can suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer. Therefore, it is believed that the resulting lithium-ion secondary battery can be made to suppress expansion and contraction during charging and discharging, and the DC resistance of the resulting lithium-ion secondary battery can also be reduced.

[0016] The negative electrode in this embodiment is preferably a negative electrode for a lithium-ion secondary battery.

[0017] [Negative electrode active material layer] The negative electrode active material layer of this embodiment comprises a silicon-based active material and a polycarboxylic acid polymer (P1) having a weight-average molecular weight Mw of 550,000 or more and 950,000 or less. The negative electrode active material layer of this embodiment further comprises, preferably, one or more components selected from the group consisting of a binder other than the polycarboxylic acid polymer (P1), graphite, and conductive additives, and more preferably, further comprises a binder other than the polycarboxylic acid polymer (P1), graphite, and conductive additives.

[0018] In this embodiment, the density of the negative electrode active material layer is preferably 0.7 g / cm³, from the viewpoint of improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer, and the performance balance of the energy density and cycle characteristics of the resulting lithium-ion secondary battery. 3 More than 2.0g / cm 3 More preferably, 0.9 g / cm³ 3 More than 1.8g / cm 3 More preferably, 1.0 g / cm³ 3 More than 1.7g / cm 3 More preferably, 1.2 g / cm³ 3 More than 1.6g / cm 3 The following applies:

[0019] In this embodiment, the thickness of the negative electrode active material layer is preferably 10 μm to 200 μm, more preferably 15 μm to 150 μm, and even more preferably 20 μm to 100 μm, from the viewpoint of improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer, and the performance balance of the energy density and rapid charging capabilities of the resulting lithium-ion secondary battery.

[0020] When the entire negative electrode active material layer of this embodiment is considered to be 100% by mass, the total content of silicon-based active material and polycarboxylic acid-based polymer (P1) in the negative electrode active material layer of this embodiment is preferably 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more and 65% by mass or less, even more preferably 20% by mass or more and 50% by mass or less, even more preferably 25% by mass or more and 45% by mass or less, and even more preferably 30% by mass or more and 40% by mass or less, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.

[0021] <Polycarboxylic acid polymer (P1)> The weight-average molecular weight Mw of the polycarboxylic acid polymer (P1) in this embodiment is 550,000 or more, preferably 570,000 or more, more preferably 590,000 or more, and even more preferably 600,000 or more, from the viewpoint of improving the adhesion between the polycarboxylic acid polymer (P1) and other materials in the negative electrode active material layer, and from the viewpoint of further suppressing the expansion and contraction of the resulting lithium-ion secondary battery during charging and discharging. The weight-average molecular weight Mw of the polycarboxylic acid polymer (P1) in this embodiment is 950,000 or less, preferably 900,000 or less, more preferably 850,000 or less, and even more preferably 800,000 or less, from the viewpoint of suppressing the generation of aggregates in the negative electrode active material layer and further reducing the DC resistance of the resulting lithium-ion secondary battery. The weight-average molecular weight Mw of the polycarboxylic acid polymer (P1) in this embodiment is 550,000 to 950,000, preferably 570,000 to 900,000, more preferably 590,000 to 850,000, and even more preferably 600,000 to 800,000, from the viewpoint of being able to suppress the generation of aggregates in the negative electrode active material layer while improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer, from the viewpoint of being able to further suppress the expansion and contraction of the resulting lithium-ion secondary battery during charging and discharging, and from the viewpoint of being able to further reduce the DC resistance of the resulting lithium-ion secondary battery.

[0022] In this embodiment, "polycarboxylic acid polymer" refers to a polymer containing an unsaturated carboxylic acid or a salt thereof as monomer units. The unsaturated carboxylic acid or its salt includes, for example, one or more selected from the group consisting of acrylic acid or its salt; methacrylic acid or its salt; maleic acid or its salt; and fumaric acid or its salt. The unsaturated carboxylic acid or its salt preferably includes one or more selected from the group consisting of acrylic acid or its salt and methacrylic acid or its salt, and more preferably includes acrylic acid or its salt. The salt of the unsaturated carboxylic acid preferably includes an alkali metal salt of the unsaturated carboxylic acid. The alkali metal salt of the unsaturated carboxylic acid includes, for example, one or more selected from the group consisting of lithium salts of unsaturated carboxylic acids, sodium salts of unsaturated carboxylic acids, and potassium salts of unsaturated carboxylic acids.

[0023] The polycarboxylic acid polymer (P1) of this embodiment preferably comprises an alkali metal salt of a polycarboxylic acid, and more preferably comprises one or more selected from the group consisting of lithium salts and sodium salts of polycarboxylic acids. In this embodiment, the alkali metal salt of the polycarboxylic acid preferably includes a lithium salt of the polycarboxylic acid, and more preferably lithium polyacrylate, from the viewpoint of improving ionic conductivity and further suppressing expansion and contraction during charging and discharging of the resulting lithium-ion secondary battery.

[0024] When the entire negative electrode active material layer of this embodiment is considered to be 100% by mass, the content of the polycarboxylic acid polymer (P1) in the negative electrode active material layer of this embodiment is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 5.0% by mass or less, even more preferably 0.6% by mass or more and 2.0% by mass or less, even more preferably 0.7% by mass or more and 1.5% by mass or less, and even more preferably 0.8% by mass or more and 1.2% by mass or less, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.

[0025] <Silicon-based active material> The silicon-based active material of the present embodiment preferably contains one or two or more selected from the group consisting of SiO x (0<x≦2), Si / C containing Si-C composite particles, and Si, more preferably contains one or two or more selected from the group consisting of SiO x (0<x≦2), and Si / C containing Si-C composite particles, and from the viewpoint of further improving the cycle characteristics of the obtained lithium ion secondary battery, it further preferably contains Si / C containing Si-C composite particles, and still more preferably contains Si-C composite particles. Further, the silicon-based active material of the present embodiment is preferably in a powder form.

[0026] The Si-C composite particles of the present embodiment preferably contain silicon and a carbon material. In the Si-C composite particles of the present embodiment, from the viewpoint of further improving the performance balance between the cycle characteristics and the energy density of the obtained lithium ion secondary battery, it is preferable that the carbon material in the Si-C composite particles includes a porous carbon material, and silicon is present in at least a part of the pores of the porous carbon material.

[0027] The porous carbon material constituting the Si-C composite particles contains, for example, one or two or more selected from the group consisting of activated carbon, aggregates of carbon fibers, aggregates of carbon nanotubes, carbon obtained by heat-treating a resin or an organic substance, hard carbon, and the like. The porous carbon material can be produced by a known production method such as a method for producing activated carbon or heat treatment of a polymer, but a commercially available product may be purchased. The porous carbon material is not limited to these as long as silicon can be generated or incorporated into the pores of the porous carbon.

[0028] In the present embodiment, the method for producing the Si-C composite particles is not particularly limited, and for example, the median diameter D 50 is 4.0 to 10.0 μm, and the specific surface area is 1100 to 1800 m 2This can be obtained by a manufacturing method in which porous carbon material in a tubular furnace is placed, the furnace is purged with argon gas, a mixed gas of silane gas and nitrogen gas containing 1-3 mol% silane gas is flowed into the tubular furnace at a flow rate of 250-350 sccm, and the process is carried out under conditions of 450-550°C, 700-800 Torr, and 90-150 minutes.

[0029] In this embodiment, a method for confirming that the Si-C composite particles contain silicon and carbon material, and that the silicon in the Si-C composite particles is present in at least a portion of the pores of the porous carbon material, is to perform elemental mapping of silicon and carbon on a cross-section of the Si-C composite particles using a scanning electron microscope, an energy-dispersive X-ray spectroscopic detector, and image analysis software, selecting secondary electrons as the detection target, and observing the results under conditions of an acceleration voltage of 3kV, 20 mapping integrations, and a magnification of 3000x.

[0030] The volume-based median diameter D of the silicon-based active material in this embodiment, as determined by laser diffraction scattering. 50 From the viewpoint of further improving the balance between the energy density and rapid charging performance of the resulting lithium-ion secondary battery, the particle size is preferably 1 μm to 20 μm, more preferably 3 μm to 17 μm, even more preferably 5 μm to 15 μm, even more preferably 6 μm to 12 μm, and even more preferably 6 μm to 10 μm.

[0031] The specific surface area of ​​the silicon-based active material in this embodiment, measured by the BET method in accordance with JIS Z8830:2013, is preferably 1 m², from the viewpoint of further improving the balance between the energy density and rapid charging performance of the resulting lithium-ion secondary battery. 2 / g or more 20m 2 / g or less, more preferably 2m 2 / g or more 15m 2 / g or less, more preferably 3m 2 / g or more 10m 2 It is less than / g.

[0032] When the entire negative electrode active material layer of this embodiment is considered to be 100% by mass, the content of silicon-based active material in the negative electrode active material layer of this embodiment is preferably 1% by mass or more and 80% by mass or less, more preferably 5% by mass or more and 60% by mass or less, even more preferably 10% by mass or more and 50% by mass or less, and even more preferably 20% by mass or more and 45% by mass or less.

[0033] <Binders other than polycarboxylic acid polymers (P1)> The negative electrode active material layer of this embodiment preferably further comprises a binder other than a polycarboxylic acid polymer (P1). In the negative electrode active material layer of this embodiment, the binder other than the polycarboxylic acid polymer (P1) includes, for example, one or more selected from the group consisting of synthetic rubbers such as styrene-butadiene rubber, butadiene rubber, chloroprene rubber, isoprene rubber, and acrylonitrile-butadiene rubber, and polysaccharides such as carboxymethylcellulose, xanthan gum, guar gum, and pectin.

[0034] The negative electrode active material layer of this embodiment preferably further contains synthetic rubber as a binder, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery. The synthetic rubber of this embodiment preferably includes styrene-butadiene rubber, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.

[0035] The volume-based median diameter D of the synthetic rubber of this embodiment, as determined by dynamic light scattering. 50 From the viewpoint of further improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer, and from the viewpoint of suppressing the expansion and contraction of the resulting lithium-ion secondary battery during charging and discharging, the wavelength is preferably 160 nm or more, more preferably 170 nm or more, even more preferably 180 nm or more, and even more preferably 190 nm or more. The volume-based median diameter D of the synthetic rubber of this embodiment, as determined by dynamic light scattering. 50From the viewpoint of improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer, and from the viewpoint of reducing the DC resistance of the resulting lithium-ion secondary battery, the wavelength is preferably 390 nm or less, more preferably 350 nm or less, even more preferably 330 nm or less, and even more preferably 310 nm or less. The volume-based median diameter D of the synthetic rubber of this embodiment, as determined by dynamic light scattering. 50 From the viewpoint of improving adhesion between the negative electrode active material layer and the negative electrode current collector layer, suppressing expansion and contraction of the resulting lithium-ion secondary battery during charging and discharging, and reducing the DC resistance of the resulting lithium-ion secondary battery, the wavelength is preferably 160 nm to 390 nm, more preferably 170 nm to 350 nm, even more preferably 180 nm to 330 nm, and even more preferably 190 nm to 310 nm.

[0036] When the entire negative electrode active material layer of this embodiment is considered to be 100% by mass, the content of binders other than the polycarboxylic acid polymer (P1) in the negative electrode active material layer of this embodiment is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 8.0% by mass or less, even more preferably 1.0% by mass or more and 5.0% by mass or less, and even more preferably 1.5% by mass or more and 3.0% by mass or less, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.

[0037] <Graphite> The negative electrode active material layer of this embodiment preferably further contains graphite. The graphite in this embodiment is not particularly limited, but from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, it preferably includes graphite containing amorphous carbon on its surface, and more preferably includes both graphite containing amorphous carbon on its surface and graphite not containing amorphous carbon on its surface. Furthermore, the graphite in this embodiment is preferably in powder form.

[0038] The median diameter D of the graphite in this embodiment, based on volume, as determined by laser diffraction scattering. 50From the viewpoint of further improving the balance between the energy density and rapid charging performance of the resulting lithium-ion secondary battery, the particle size is preferably 1 μm to 30 μm, more preferably 5 μm to 25 μm, even more preferably 10 μm to 20 μm, and even more preferably 10 μm to 15 μm.

[0039] The specific surface area of ​​the graphite in this embodiment, measured by the BET method in accordance with JIS Z8830:2013, is preferably 0.5 m², from the viewpoint of further improving the balance between the energy density and rapid charging performance of the resulting lithium-ion secondary battery. 2 / g or more 5.0m 2 / g or less, more preferably 0.8m 2 / g or more 4m 2 / g or less, more preferably 1.0m 2 / g or more 3.0m 2 It is less than / g.

[0040] When the entire negative electrode active material layer of this embodiment is considered to be 100% by mass, the graphite content in the negative electrode active material layer of this embodiment is preferably 20% by mass or more and 99% by mass or less, more preferably 40% by mass or more and 95% by mass or less, even more preferably 50% by mass or more and 90% by mass or less, and even more preferably 55% by mass or more and 80% by mass or less.

[0041] <Conductive additive> The negative electrode active material layer of this embodiment preferably further includes a conductive additive from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the resulting lithium-ion secondary battery.

[0042] The conductive additive in the negative electrode active material layer of this embodiment includes, for example, one or more selected from the group consisting of carbon fibers such as carbon nanofibers; carbon black such as acetylene black and Ketjen black; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. The conductive additive in the negative electrode active material layer of this embodiment preferably includes a carbon material, from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the resulting lithium-ion secondary battery. The carbon material of this embodiment preferably includes carbon nanotubes from the viewpoint of further improving the performance balance between energy density and cycle characteristics of the resulting lithium-ion secondary battery, and more preferably includes single-walled carbon nanotubes from the viewpoint of maintaining the electrical path even when expansion and contraction occur in the negative electrode active material layer.

[0043] The specific surface area of ​​the carbon nanotubes in this embodiment, as measured by the nitrogen adsorption BET method, is preferably 300 m², from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the resulting lithium-ion secondary battery. 2 / g or more, more comfortably 350m 2 / g or more, more preferably 400m 2 / g or more, more preferably 450m 2 / g or more, more preferably 500m 2 It is 1500 m² or more. There is no particular upper limit to the specific surface area of ​​the carbon nanotubes in this embodiment, but for example, 1500 m² 2 It may be less than / g, and 1200m 2 It may be less than / g, and 1000m 2 It may be less than / g. From the viewpoint of further improving the performance balance between energy density and cycle characteristics of the resulting lithium-ion secondary battery, the specific surface area of ​​the carbon nanotube in this embodiment is preferably 300 m². 2 / g or more 1500m 2 / g or less, more preferably 350m 2 / g or more 1200m 2 / g or less, more preferably 400m 2 / g or more 1000m 2 / g or less, more preferably 450m 2 / g or more 1000m 2 / g or less, more preferably 500m 2 / g or more 1000m 2 It is less than / g. The specific surface area of ​​carbon nanotubes can be measured, for example, by the method described in the examples.

[0044] The aspect ratio of the carbon nanotube in this embodiment is preferably 10 or more, more preferably 100 or more, even more preferably 500 or more, even more preferably 1000 or more, and even more preferably 1500 or more, from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the lithium-ion secondary battery. There is no particular upper limit to the aspect ratio of the carbon nanotube in this embodiment, but it may be, for example, 10000 or less, 8000 or less, 5000 or less, 4000 or less, or 3000 or less. The aspect ratio of the carbon nanotubes in this embodiment is preferably 10 to 10000, more preferably 100 to 8000, even more preferably 500 to 5000, even more preferably 1000 to 4000, and even more preferably 1500 to 3000, from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the lithium-ion secondary battery. The aspect ratio of carbon nanotubes can be measured, for example, by the method described in the examples.

[0045] When the entire negative electrode active material layer of this embodiment is considered to be 100% by mass, the content of the conductive additive in the negative electrode active material layer of this embodiment is preferably 0.01% by mass or more and 10.0% by mass or less, more preferably 0.05% by mass or more and 5.0% by mass or less, even more preferably 0.08% by mass or more and 1.0% by mass or less, and even more preferably 0.1% by mass or more and 0.5% by mass or less, from the viewpoint of further improving the performance balance of the energy density and cycle characteristics of the resulting lithium-ion secondary battery.

[0046] [Negative electrode current collector layer] The negative electrode current collector layer of this embodiment includes a negative electrode current collector formed from one or more materials selected from the group consisting of, for example, aluminum, stainless steel, nickel, titanium, and alloys thereof, and preferably includes a negative electrode current collector formed from copper. The shape of the negative electrode current collector is, for example, foil, flat plate, mesh, etc., and is preferably foil. The negative electrode current collector layer of this embodiment preferably includes copper foil.

[0047] In this embodiment, the thickness of the negative electrode current collector layer is preferably 1 μm to 20 μm, more preferably 2 μm to 18 μm, even more preferably 3 μm to 16 μm, even more preferably 4 μm to 14 μm, even more preferably 5 μm to 12 μm, and even more preferably 6 μm to 10 μm, from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the resulting lithium-ion secondary battery.

[0048] [Negative electrode characteristics] The peel strength (hereinafter also referred to as peel strength) of the negative electrode of this embodiment, obtained by the following method 1, is preferably 10 N / mm or more, more preferably 11 N / mm or more, and even more preferably 12 N / mm or more, from the viewpoint of further improving the adhesion between the negative electrode active material layer and the negative electrode current collector layer. There is no particular upper limit to the peel strength, but for example it may be 50 N / mm or less, 40 N / mm or less, or 30 N / mm or less. The peel strength is, for example, 10 N / mm or more and 50 N / mm or less, but may also be 11 N / mm or more and 40 N / mm or less, or 12 N / mm or more and 30 N / mm or less.

[0049] (Method 1) The negative electrode of this embodiment is cut to a size of 10 mm x 100 mm to prepare a test specimen. Then, using a tensile testing machine, the tensile strength per unit area of ​​the test specimen is measured at a tensile speed of 10 mm / min and a temperature of 25°C to obtain a value of 15 N / mm². 2The test specimen is pulled until it reaches this point. Next, using a peel tester, the peel strength is measured by pulling the negative electrode active material layer of the test specimen in a 90° direction under conditions of a pulling speed of 50 mm / min and a temperature of 25°C. Furthermore, the peel strength can be measured more specifically by the method described in the examples.

[0050] The cell expansion rate (hereinafter also referred to as the cell expansion rate) of the negative electrode of this embodiment, obtained by the following method 2, is preferably 4.1% or less, more preferably 4.0% or less, and even more preferably 3.9% or less, from the viewpoint of reducing the expansion of the resulting lithium-ion secondary battery. There is no particular lower limit to the cell expansion rate, but it may be, for example, 0.0% or more, 1.0% or more, or 2.0% or more. The cell expansion rate is, for example, 0.0% to 4.1%, may be 1.0% to 4.0%, or 2.0% to 3.9%.

[0051] (Method 2) For cells prepared according to the <Method for Preparing Cells> described below, measure the cell expansion rate according to the <Method for Measuring Cell Expansion Rate> described below. The cell expansion rate can be measured more specifically by the method described in the examples. <How to create cells> Lithium nickel-cobalt manganese oxide (LiNi 0.9 Co 0.05 Mn 0.05 A cathode active material slurry is prepared by adding N-methyl-2-pyrrolidone to a solid component consisting of 97.5 parts by mass of O2, 1.5 parts by mass of polyvinylidene fluoride, and 1.0 part by mass of multi-walled carbon nanotubes. Then, the cathode active material slurry is applied to both sides of an aluminum foil, for example, to an initial charge capacity of 4.0 mAh / cm² per unit area. 2 After coating in this manner, it is dried to obtain a positive electrode laminate consisting of a positive electrode active material layer and aluminum foil. Next, the positive electrode laminate is subjected to a process where the density of the positive electrode active material layer is 3.50 g / cm³. 3 Press it in this manner to obtain the positive electrode. Next, an electrode stack, in which the negative electrode, separator, positive electrode, separator, and negative electrode are arranged in that order, and a non-aqueous electrolyte is placed inside a laminated casing. Then, a negative electrode tab is connected to the negative electrode and a positive electrode tab is connected to the positive electrode, and the laminated casing is sealed to create a cell. <Method for measuring cell expansion coefficient> The cell is placed in a constant temperature bath at 25°C. Then, it is charged at a constant current at a charge rate of 0.05C until the upper voltage reaches 4.25V. After the voltage reaches 4.25V, it is charged at a constant voltage until the total charging time is 22 hours. Then, it is discharged at a constant current at a discharge rate of 1 / 3C until the lower voltage reaches 2.5V. After discharge, the cell is left to stand in a constant temperature bath at 45°C for 48 hours. Then, the cell expansion rate is calculated from the following formula (1). Equation (1): (Cell expansion rate) = {(Cell thickness after standing in a 45°C constant temperature bath for 48 hours after charging and discharging) - (Cell thickness before charging)} / (Cell thickness before charging) × 100

[0052] The DC resistance of the negative electrode in this embodiment, obtained by method 3 below (hereinafter also referred to as DC resistance), is preferably 5.0 mΩ or less, more preferably 4.9 mΩ or less, and even more preferably 4.8 mΩ or less, from the viewpoint of improving the conductivity of the resulting lithium-ion secondary battery. There is no particular lower limit to the DC resistance, but for example, it may be 0.0 mΩ or more, 1.0 mΩ or more, or 2.0 mΩ or more. The DC resistance may be, for example, 0.0 mΩ or more and 5.0 mΩ or less, but may also be 1.0 mΩ or more and 4.9 mΩ or less, or 2.0 mΩ or more and 4.8 mΩ or less.

[0053] (Method 3) The DC resistance of the cells prepared according to the above <Method for preparing cells> is measured according to the <Method for measuring DC resistance> described below. Furthermore, the DC resistance can be measured more specifically by the method described in the examples. <Method for measuring DC resistance> The cell is placed in a constant temperature bath at 25°C. Next, the cell is charged to 50% of its State of Charge (SOC). Then, using a charge / discharge device, current is applied to the cell at 0.5C for 30 seconds, 1.0C for 30 seconds, and 2.0C for 30 seconds, and the voltage at 0.5C, 1.0C, and 2.0C is measured. Next, points corresponding to each voltage are plotted on a graph with current on the x-axis and voltage on the y-axis, and the slope of the three points is calculated to obtain the DC resistance.

[0054] 2. Lithium-ion rechargeable batteries The lithium-ion secondary battery of this embodiment comprises the negative electrode, positive electrode, and separator of this embodiment. Because the lithium-ion secondary battery of this embodiment includes the negative electrode of this embodiment, its cycle characteristics are improved.

[0055] The lithium-ion secondary battery of this embodiment will be described with reference to the figures. Figure 1 is a schematic cross-sectional view illustrating an example of the lithium-ion secondary battery of this embodiment. As shown in Figure 1, the lithium-ion secondary battery 10 comprises the negative electrode, positive electrode, and separator 5 of this embodiment.

[0056] The lithium-ion secondary battery 10 comprises a positive electrode having a positive electrode active material layer 1 and a positive electrode current collector layer 3, and a negative electrode having a negative electrode active material layer 2 and a negative electrode current collector layer 4. The positive electrode and the negative electrode are stacked via a separator 5 so that, for example, the positive electrode active material layer 1 and the negative electrode active material layer 2 face each other, thereby forming an electrode pair. This electrode pair is housed in a container formed by, for example, an outer casing 6, 7. A positive electrode tab 9 is connected to the positive electrode current collector layer 3, and a negative electrode tab 8 is connected to the negative electrode current collector layer 4, with the positive electrode tab 9 and the negative electrode tab 8 extending out of the container. An electrolyte is sealed inside the container. The lithium-ion secondary battery 10 can also have a structure in which an electrode group, each consisting of multiple stacked electrode pairs, is housed in the container.

[0057] The lithium-ion secondary battery 10 can be manufactured according to known methods. The electrodes are, for example, laminates, wound bodies, etc. The casing is, for example, a metal casing, an aluminum laminate casing, etc. The shape of the battery is, for example, coin-type, button-type, sheet-type, cylindrical, prismatic, flat-type, etc.

[0058] [Positive electrode] In the lithium-ion secondary battery of this embodiment, the positive electrode preferably comprises a positive electrode active material layer containing a positive electrode active material and a positive electrode current collector layer. The positive electrode active material layer of this embodiment is provided, for example, on the positive electrode current collector layer of this embodiment.

[0059] The positive electrode active material in the positive electrode active material layer of this embodiment is, for example, a composite oxide of lithium and a transition metal such as lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-cobalt-manganese composite oxide; transition metal sulfides such as TiS2, FeS, MoS2; and MnO, V2O5, V6O 13 It includes one or more selected from the group consisting of transition metal oxides such as TiO2, and olivine-type lithium phosphate oxide. The positive electrode active material in the positive electrode active material layer of this embodiment preferably includes a composite oxide of lithium and a transition metal, more preferably includes one or more composite oxides selected from the group consisting of lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, lithium-nickel-cobalt-manganese-aluminum composite oxide, and lithium-nickel-cobalt-manganese composite oxide, and even more preferably includes a lithium-nickel-cobalt-manganese composite oxide.

[0060] When the total amount of the positive electrode active material layer in this embodiment is considered to be 100% by mass, the content of the positive electrode active material in the positive electrode active material layer of this embodiment is preferably 50.0% by mass or more and 99.9% by mass or less, more preferably 75.0% by mass or more and 99.5% by mass or less, even more preferably 85.0% by mass or more and 99.0% by mass or less, even more preferably 90.0% by mass or more and 98.5% by mass or less, and even more preferably 95.0% by mass or more and 98.0% by mass or less.

[0061] The positive electrode active material layer of this embodiment preferably further includes a binder. The binder in the positive electrode active material layer of this embodiment includes one or more selected from the group consisting of, for example, fluorine-based binders such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), and aqueous binders such as styrene-butadiene rubber.

[0062] The positive electrode active material layer of this embodiment preferably further contains a conductive additive. The conductive additive in the positive electrode active material layer of this embodiment includes, for example, one or more selected from the group consisting of carbon fibers such as carbon nanofibers; carbon black such as acetylene black and Ketjen black; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes.

[0063] The positive electrode current collector layer of this embodiment includes a positive electrode current collector formed from one or more materials selected from the group consisting of, for example, aluminum, stainless steel, nickel, titanium, and alloys thereof. The shape of the positive electrode current collector is, for example, foil, flat plate, mesh, etc. The thickness of the positive electrode current collector is, for example, 1 μm or more and 50 μm or less.

[0064] [Separator] The separator in this embodiment is, for example, a porous membrane, woven fabric, or nonwoven fabric made of resin. The resin component constituting the separator includes, for example, one or more selected from the group consisting of polyolefin resins such as polypropylene and polyethylene; polyester resins; acrylic resins; styrene resins; and nylon resins. Furthermore, if necessary, the separator may include a layer containing inorganic particles. The inorganic particles include, for example, one or more selected from the group consisting of insulating oxides, nitrides, sulfides, and carbides.

[0065] [Electrolyte] The electrolyte of this embodiment preferably includes a non-aqueous electrolyte obtained by dissolving a lithium salt in an organic solvent. The organic solvent includes, for example, one or more selected from the group consisting of cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), and butylene carbonate (BC); linear carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC); aliphatic carboxylic acid esters; γ-lactones such as γ-butyrolactone; linear ethers; and cyclic ethers. The lithium salt includes, for example, one or more selected from the group consisting of lithium hexafluoride phosphate (LiPF6), lithium borofluoride (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium perchlorate (LiClO4).

[0066] [Exterior] The exterior of this embodiment is, for example, a flexible film, a can case, or a case made of a flexible film, and from the viewpoint of reducing the weight of the lithium-ion secondary battery, a flexible film is preferably used. A flexible film is, for example, a laminate in which resin layers are provided on the front and back surfaces of a metal layer that serves as a base material. At least one surface of the metal layer is provided with a heat-sealable resin layer, for example, made of modified polyolefin. On the surface opposite to the surface with the heat-sealable resin layer, a resin layer, for example, made of nylon resin, polyester resin, etc. The metal layer is made of a material that has barrier properties, such as preventing leakage of electrolyte and intrusion of moisture from the outside, and is made of, for example, aluminum, stainless steel, etc. The exterior body of this embodiment can be formed by facing the heat-sealable resin layers of the flexible film toward each other and heat-sealing the area around the portion that houses the electrode laminate.

[0067] 3. Lithium-ion secondary battery module The lithium-ion secondary battery module of this embodiment is equipped with the lithium-ion secondary battery of this embodiment. Because the lithium-ion secondary battery module of this embodiment is equipped with the lithium-ion secondary battery of this embodiment, its cycle characteristics are improved.

[0068] The lithium-ion secondary battery module of this embodiment preferably comprises two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment preferably further comprises a housing capable of housing the lithium-ion secondary battery of this embodiment. The lithium-ion secondary battery module of this embodiment preferably further includes one or more selected from the group consisting of a protection circuit to protect the lithium-ion secondary battery from overcurrent; a balance circuit to equalize the voltage between the electrodes of the lithium-ion secondary battery; a controller to control the lithium-ion secondary battery; a cooler capable of cooling the lithium-ion secondary battery; and a heater capable of heating the lithium-ion secondary battery.

[0069] The lithium-ion secondary battery module of this embodiment can be used in a battery system comprising multiple electrically connected lithium-ion secondary battery modules and a battery control system. The battery system includes, for example, one or more types selected from the group consisting of battery packs, stationary battery systems, battery systems for vehicle power, battery systems for vehicle auxiliary equipment, and battery systems for emergency power supplies.

[0070] The embodiments of the present invention have been described above, but these are merely examples, and various other configurations can also be adopted.

[0071] It should be noted that the present invention is not limited to the embodiments described above, and any modifications, improvements, etc., that can achieve the objectives of the present invention are included in the present invention. [Examples]

[0072] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto.

[0073] <Measurement of weight-average molecular weight (Mw) of polycarboxylic acid polymers> The weight-average molecular weight (Mw) of polycarboxylic acid polymers is calculated by first measuring the absolute molecular weight (viscosity method) using a gel permeation chromatography (GPC) light scattering system equipped with a triple detector under the following measurement conditions. (Measurement conditions) GPC light scattering device: MODEL302 (manufactured by VISCOTEK.Co.) Columns: SB807 + SB806 + SB804 (manufactured by Resonaq) Carrier: 0.2M sodium nitrate Column temperature: 40℃ Flow rate: 0.5mL / min Injection volume: 500μL Concentration of polycarboxylic acid polymer: 0.09 mg / mL

[0074] <Median diameter D of synthetic rubber> 50 Measurement > The median diameter D is determined from the volume frequency particle size distribution measured by dynamic light scattering using a dynamic light scattering particle size distribution analyzer (LB-500, manufactured by Horiba, Ltd.). 50 Here, the median diameter D of the synthetic rubber was determined. 50 Measurements were taken in an aqueous emulsion state. Five measurements were performed, and the arithmetic mean of each value was used.

[0075] <Measurement of specific surface area of ​​negative electrode active material and conductive additive> The specific surface area was measured using a fully automatic specific surface area measuring device (Macsorb HM-1208, manufactured by Mountec Co., Ltd.) in accordance with JIS Z 8830:2013, employing the BET flow method and the single-point method.

[0076] <Median diameter D of the negative electrode active material> 50 Measurement > The median diameter D at which the cumulative value reaches 50% is determined from the volume frequency particle size distribution measured by laser diffraction scattering using a laser diffraction particle size distribution analyzer (SALD-2300, manufactured by Shimadzu Corporation). 50 The following was determined. Here, the negative electrode active material was suspended in a dispersion medium (0.1% by mass sodium hexametaphosphate aqueous solution), ultrasonically dispersed, and then measured. Five measurements were taken, and the arithmetic mean of the obtained values ​​was adopted.

[0077] <Measurement of the aspect ratio (fiber length / fiber diameter) of carbon nanotubes> Using a scanning electron microscope, carbon nanotubes were observed under conditions of 5000x magnification and a field of view of 20 μm × 20 μm. The fiber diameter and fiber length of the carbon nanotubes were measured, and the aspect ratio was calculated. A total of 100 samples were measured, and the average values ​​were used for each.

[0078] Next, the negative electrodes for each example were prepared using the following procedure, and the aggregates were evaluated and the peeling strength was measured. The results are shown in Table 1.

[0079] <Fabrication of the negative electrode> A negative electrode active material slurry was prepared by adding an appropriate amount of water to the solid components with the composition shown in Table 1. Next, the negative electrode active material slurry was applied to an 8 μm thick copper foil, which served as the negative electrode current collector, with an initial charge capacity of 4.7 mAh / cm² per unit area. 2 After coating in this manner, the material was dried to obtain a negative electrode laminate consisting of a negative electrode active material layer and copper foil. Next, using a roll press, the negative electrode laminate was processed so that the density of the negative electrode active material layer was 1.40 g / cm³. 3 The material was pressed in this manner to obtain the negative electrode for each example.

[0080] <Evaluation of aggregates> Cases where no aggregates formed during negative electrode fabrication were evaluated as A, and cases where aggregates formed during negative electrode fabrication were evaluated as B. Furthermore, because aggregates formed during the negative electrode fabrication process, peel strength, cell expansion coefficient, and DC resistance measurements were not performed in Comparative Example 1.

[0081] <Measurement of peel strength> The negative electrode of each example was cut to a size of 10 mm x 100 mm to prepare test specimens. Then, using a tensile testing machine (IMADA Corporation's digital force gauge "ZP-5N" and electric stage "MX-500N"), the tensile strength per unit area of ​​the test specimen was measured at a tensile speed of 10 mm / min and a temperature of 25°C, and the result was 15 N / mm². 2 The test specimen was pulled until it reached this point. Next, using a peel tester (a digital force gauge "ZP-5N" and an electric stage "MX-500N" manufactured by IMADA Corporation), the peel strength was measured by pulling the negative electrode active material layer of the test specimen at a 90° angle under conditions of a pulling speed of 50 mm / min and a temperature of 25°C.

[0082] Next, cells for each example were prepared using the following procedure, and the cell expansion rate and DC resistance were calculated. The results are shown in Table 1.

[0083] <Fabrication of the positive electrode> Lithium nickel-cobalt manganese oxide (LiNi 0.9 Co 0.05 Mn 0.05 97.5 parts by mass of O2, 1.5 parts by mass of polyvinylidene fluoride (manufactured by Kureha Corporation), and multi-walled carbon nanotubes (aspect ratio: 150, specific surface area: 275 m²). 2 A positive electrode active material slurry was prepared by adding an appropriate amount of N-methyl-2-pyrrolidone to a solid content of 1.0 part by mass (g). Next, the positive electrode active material slurry was applied to both sides of a 12 μm thick aluminum foil, which served as the positive electrode current collector, with an initial charge capacity of 4.0 mAh / cm² per unit area. 2 After coating in this manner, the material was dried to obtain a positive electrode laminate consisting of a positive electrode active material layer and aluminum foil. Next, using a roll press machine, the positive electrode laminate was processed so that the density of the positive electrode active material layer was 3.50 g / cm³. 3 The positive electrode was obtained by pressing it in this manner.

[0084] <Preparation of non-aqueous electrolyte> The organic solvent was prepared by adjusting the volume ratio of ethylene carbonate to ethyl methyl carbonate to 3:7. Then, lithium hexafluoride phosphate was added to the organic solvent as a supporting salt, and fluoroethylene carbonate was added as an additive. Lithium hexafluoride phosphate was added to the organic solvent to a concentration of 1.2 mol / L. Fluoroethylene carbonate was added to the organic solvent to a concentration of 6% by mass relative to the organic solvent.

[0085] <Cell creation> Two negative electrodes and one positive electrode for each example were cut to 30 mm x 30 mm. Next, an electrode laminate was fabricated by arranging the negative electrode, separator, positive electrode, separator, and negative electrode in that order. For the separator, a 10 μm thick microporous polyethylene film with ceramic coating on both sides was used. Next, the electrode laminate and a non-aqueous electrolyte were placed inside a laminate casing molded from a film mainly composed of aluminum. Then, a negative electrode tab was connected to the negative electrode and a positive electrode tab was connected to the positive electrode, and the periphery of the laminate casing was sealed to fabricate the cell for each example. Here, one end of the positive electrode tab was connected to the positive electrode, and the other end was extended outside the laminate casing. Similarly, one end of the negative electrode tab was connected to the negative electrode, and the other end was extended outside the laminate casing.

[0086] <Measurement of Cell Expansion Rate> Each cell was placed in a constant temperature bath at 25°C. Then, it was charged at a constant current at a charge rate of 0.05C until the upper voltage limit reached 4.25V. After reaching 4.25V, it was charged at a constant voltage until the total charging time was 22 hours. Next, it was discharged at a constant current at a discharge rate of 1 / 3C until the lower voltage limit reached 2.5V. After discharge, the cells were left to stand in a constant temperature bath at 45°C for 48 hours. Finally, the cell expansion rate was calculated using the above formula (1).

[0087] <Measuring DC resistance> Each cell was placed in a constant temperature bath at 25°C. The cells were then charged to a State of Charge (SOC) of 50%. Next, using a charge / discharge device (Toyo System Co., Ltd., TYS-32TU700), current was applied to the cells at 0.5C for 30 seconds, 1.0C for 30 seconds, and 2.0C for 30 seconds. The voltages at 0.5C, 1.0C, and 2.0C were measured. Then, points corresponding to each voltage were plotted on a graph with current on the x-axis and voltage on the y-axis. The slopes of the three points were calculated to determine the DC resistance. The slopes of the three points were determined using the least squares method to find the slopes of the approximate straight line.

[0088] [Table 1]

[0089] Details of each component in Table 1 are as follows: <Negative electrode active material> • Silicon-based active materials Si / C (Si-C composite particles, median diameter D) 50 :5μm) ·graphite Graphite 1 (artificial graphite with amorphous carbon coating on the surface, median diameter D) 50 :13μm, specific surface area: 1.4m 2 / g) Graphite 2 (artificial graphite that does not contain amorphous carbon on the surface, median diameter D) 50 :10μm, specific surface area: 1.8m 2 / g) <Conductive additive> Single-walled carbon nanotubes (aspect ratio: 2000, specific surface area: 500 m²) 2 / g)

[0090] <Binder> (Polycarboxylic acid polymers) Polycarboxylic acid polymer 1: Lithium polyacrylate (weight-average molecular weight Mw: 600,000) (also called polymer 1). Polycarboxylic acid polymer 2: Lithium polyacrylate (weight-average molecular weight Mw: 700,000) (also called polymer 2). Polycarboxylic acid-based polymer 3: Lithium polyacrylate (weight average molecular weight Mw: 800,000) (also referred to as Polymer 3). Polycarboxylic acid-based polymer 4: Sodium polyacrylate (weight average molecular weight Mw: 700,000) (also referred to as Polymer 4). Polycarboxylic acid-based polymer 5: Lithium polyacrylate (weight average molecular weight Mw: 1,000,000) (also referred to as Polymer 5). Polycarboxylic acid-based polymer 6: Lithium polyacrylate (weight average molecular weight Mw: 500,000) (also referred to as Polymer 6).

[0091] (Synthetic Rubber) Synthetic Rubber 1: Styrene-butadiene-based rubber (aqueous emulsion, median diameter D 50 : 250 nm) Synthetic Rubber 2: Styrene-butadiene-based rubber (aqueous emulsion, median diameter D 50 : 200 nm) Synthetic Rubber 3: Styrene-butadiene-based rubber (aqueous emulsion, median diameter D 50 : 300 nm) Note that the parts by mass of the synthetic rubber in Table 1 represent parts by mass of the solid content of the aqueous emulsion.

[0092] <Preparation of Si-C Composite Particles> A porous carbon material (median diameter D 50 : 5 μm, specific surface area: 1300 m 2 / g) was placed in a tubular furnace, the inside of the tubular furnace was purged with argon gas, then a mixed gas of 2 mol% silane gas and 98 mol% nitrogen gas was flowed into the tubular furnace at a flow rate of 300 sccm, and the treatment was performed by holding the conditions at 500°C, 760 Torr for 120 minutes. Next, the product was cooled to room temperature to obtain Si-C composite particles.

[0093] Cross-sections of the obtained Si-C composite particles were analyzed using a scanning electron microscope (Hitachi High-Tech Corporation, SU3500), an energy-dispersive X-ray spectroscopy detector (Oxford Instruments, Ultim Max 40), and image analysis software (Oxford Instruments, Aztec). Secondary electrons were selected as the target of detection, and elemental mapping of silicon and carbon was performed under the conditions of an acceleration voltage of 3kV, 20 mapping integrations, and a magnification of 3000x. This confirmed that the Si-C composite particles contain silicon, and that silicon is present in at least a portion of the pores of the porous carbon material within the Si-C composite particles. [Explanation of Symbols]

[0094] 1 Cathode active material layer 2 Negative electrode active material layer 3. Positive electrode current collector layer 4. Negative electrode current collector layer 5 Separators 6. Exterior 7. Exterior 8 Negative Electrode Tabs 9 Positive Tab 10 Lithium-ion rechargeable batteries

Claims

1. It comprises a negative electrode active material layer and a negative electrode current collector layer, The negative electrode comprises a silicon-based active material layer and a polycarboxylic acid polymer (P1) having a weight-average molecular weight Mw of 550,000 or more and 950,000 or less.

2. The negative electrode according to claim 1, wherein the polycarboxylic acid polymer (P1) comprises an alkali metal salt of a polycarboxylic acid.

3. The negative electrode according to claim 2, wherein the alkali metal salt of the polycarboxylic acid includes a lithium salt of the polycarboxylic acid.

4. The negative electrode according to claim 2, wherein the alkali metal salt of the polycarboxylic acid comprises lithium polyacrylate.

5. The aforementioned silicon-based active material is SiO x The negative electrode according to any one of claims 1 to 4, comprising one or more selected from the group consisting of (0 < x ≤ 2), Si / C including Si-C composite particles, and Si.

6. The negative electrode according to any one of claims 1 to 5, wherein, when the entire negative electrode active material layer is considered to be 100% by mass, the content of the polycarboxylic acid polymer (P1) in the negative electrode active material layer is 0.1% by mass or more and 10% by mass or less.

7. The negative electrode according to any one of claims 1 to 6, wherein, when the entire negative electrode active material layer is considered to be 100% by mass, the content of the silicon-based active material in the negative electrode active material layer is 1% by mass or more and 80% by mass or less.

8. The negative electrode according to any one of claims 1 to 7, wherein the negative electrode active material layer further comprises synthetic rubber as a binder.

9. The negative electrode according to claim 8, wherein the synthetic rubber includes a styrene-butadiene rubber.

10. The negative electrode according to any one of claims 1 to 9, wherein the peel strength by the method 1 described below is 10 N / mm or more. (Method 1) The negative electrode is cut to a size of 10 mm x 100 mm to prepare a test specimen. Then, using a tensile testing machine, the tensile strength per unit area of ​​the test specimen is measured at a tensile speed of 10 mm / min and a temperature of 25°C, and the result is 15 N / mm². 2 The test piece is pulled until it reaches this point. Next, using a peel tester, the peel strength is measured by pulling the negative electrode active material layer of the test piece in a 90° direction under conditions of a pulling speed of 50 mm / min and a temperature of 25°C.

11. The negative electrode according to any one of claims 1 to 10, wherein the cell expansion rate by method 2 below is 4.1% or less. (Method 2) For cells prepared according to the method described below, the cell expansion rate is measured according to the method described below. <How to create cells> Lithium nickel-cobalt manganese oxide (LiNi 0.9 Co 0.05 Mn 0.05 O 2 A cathode active material slurry is prepared by adding N-methyl-2-pyrrolidone to a solid component consisting of 97.5 parts by mass of ) 1.5 parts by mass of polyvinylidene fluoride and 1.0 part by mass of multilayer carbon nanotubes. Next, the cathode active material slurry is applied to both sides of an aluminum foil and dried to obtain a cathode laminate consisting of a cathode active material layer and the aluminum foil. Next, the cathode laminate is subjected to a procedure where the density of the cathode active material layer is 3.50 g / cm³. 3 Press it in this manner to obtain the positive electrode. Next, an electrode laminate in which the negative electrode, separator, positive electrode, separator, and negative electrode are arranged in this order, and a non-aqueous electrolyte is placed inside a laminate casing. Then, a negative electrode tab is connected to the negative electrode and a positive electrode tab is connected to the positive electrode, and the laminate casing is sealed to create a cell. <Method for measuring cell expansion rate> The cell is placed in a constant temperature bath at 25°C. Next, it is charged with a constant current at a charge rate of 0.05C until the upper limit voltage reaches 4.25V, and after the voltage reaches 4.25V, it is charged with a constant voltage until the total charging time is 22 hours. Next, it is discharged with a constant current at a discharge rate of 1 / 3C until the lower limit voltage reaches 2.5V. After discharge, the cell is left to stand in a constant temperature bath at 45°C for 48 hours. Next, the cell expansion rate is calculated from the following formula (1). Equation (1): (The cell expansion rate) = {(The cell thickness after being left to stand for 48 hours in the constant temperature bath at 45°C after charging and discharging) - (The cell thickness before charging)} / (The cell thickness before charging) × 100

12. The negative electrode according to any one of claims 1 to 11, wherein the DC resistance obtained by method 3 below is 5.0 mΩ or less. (Method 3) For cells prepared according to the method described below, the DC resistance is measured according to the method described below. <How to create cells> Lithium nickel cobalt manganese oxide (LiNi 0.9 Co 0.05 Mn 0.05 O 2 ) To a solid content consisting of 97.5 parts by mass, 1.5 parts by mass of polyvinylidene fluoride and 1.0 part by mass of multi-walled carbon nanotubes, N-methyl-2-pyrrolidone is added to prepare a positive electrode active material slurry. Next, the positive electrode active material slurry is applied to both surfaces of an aluminum foil and then dried to obtain a positive electrode laminate composed of a positive electrode active material layer and the aluminum foil. Next, the positive electrode laminate is subjected to pressing such that the density of the positive electrode active material layer is 3.50 g / cm 3 to obtain a positive electrode. Next, an electrode laminate in which the negative electrode, separator, positive electrode, separator, and negative electrode are arranged in this order, and a non-aqueous electrolyte is placed inside a laminate casing. Then, a negative electrode tab is connected to the negative electrode and a positive electrode tab is connected to the positive electrode, and the laminate casing is sealed to create a cell. <Method for measuring DC resistance> The cell is placed in a constant temperature bath at 25°C. Then, the cell is charged to 50% of its state of charge (SOC). Next, using a charge / discharge device, current is applied to the cell at 0.5C for 30 seconds, 1.0C for 30 seconds, and 2.0C for 30 seconds, and the voltage at 0.5C, 1.0C, and 2.0C is measured, respectively. Then, on a graph with the current value on the horizontal axis and the voltage on the vertical axis, points corresponding to each voltage are plotted, and the slope of the three points is calculated to obtain the DC resistance.

13. The negative electrode according to any one of claims 1 to 12, wherein the negative electrode active material layer further comprises graphite.

14. The negative electrode according to claim 13, wherein, when the entire negative electrode active material layer is considered to be 100% by mass, the graphite content in the negative electrode active material layer is 20% by mass or more and 99% by mass or less.

15. The negative electrode according to any one of claims 1 to 14, wherein the negative electrode active material layer further comprises a conductive additive.

16. The negative electrode according to claim 15, wherein the conductive additive comprises a carbon material.

17. The negative electrode according to claim 16, wherein the carbon material includes carbon nanotubes.

18. The negative electrode according to any one of claims 1 to 17, wherein the negative electrode current collector layer includes copper foil.

19. A negative electrode according to any one of claims 1 to 18, Positive electrode and, A lithium-ion secondary battery equipped with a separator.

20. A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in claim 19.

Citation Information

Patent Citations

  • Method for manufacturing negative electrode, and negative electrode

    JP2023156004A

  • Lithium-ion cells having silicon-based active materials and negative electrodes using water-based binders with good adhesive and cohesive strength

    JP2023533509A